A rapid HPLC method for the determination of sulphonamides and trimethoprim in feed premixes - Tzamaloukas, Ouranios; Goulas, Vlasios; Angastinioti Moditi, Chrystalleni; Andreou, Anisimova (My University, 2014)
A simple HPLC method for the simultaneous determination of sulphadimidine, sulphadiazine, sulphamethoxazole and trimethoprim antibiotics in medicated feeds has been developed, validated, and applied to commercial feed premixes. Ultrasound-assisted extraction was used for the recovery of the studied antibiotics without the need for a further clean-up step. The sulphonamides and trimethoprim were separated on a Symmetry C18 (5 μm, 4.6 × 250 mm) column using 10-min isocratic elution and UV detection at 254 nm. The results showed that the method is robust with adequate recovery (minimum 95.19%), satisfactory repeatability (1.39%-2.69%) and intermediate precision (1.36%-4.16%), as shown by the validation assessment herein. The advantages of the proposed method are the speed, the ease of the clean-up protocol, and the low cost of the needed instrumentation, rendering it highly applicable to the feed industry.
Keywords: Additives; Antibiotics; Feed premixes; Medicated feed; Sulpha